PENINGKATAN KETERAMPILAN BERBICARA MELALUI METODE STORYTELLING PADA SISWA KELAS IV SD - Achmad Sumali; Luqman Rohmad Maghribi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low speaking skills of fourth-grade elementary school students, influenced by various multidimensional learning barriers, including communication anxiety (glossophobia). The purpose of this study is to evaluate the effectiveness of the storytelling method in improving students' speaking skills classically. The method used is Classroom Action Research (CAR) following the Kemmis and McTaggart model, conducted in two cycles at SDN 01 Pamulang with 20 students as subjects. Data were collected through speaking performance tests and observations of learning activities, which were then analyzed using descriptive comparative techniques. The results of the study show a significant transformation in students' verbal abilities; there was a performance surge from the pre-cycle stage to Cycle II, reaching a classical completeness indicator of ≥85%. This success was driven by the synergy between the use of local wisdom (Majalengka Wisdom), the integration of Artificial Intelligence (AI) features as a creativity stimulant, and the support of a professional school management ecosystem through reflective academic supervision. The conclusion of this study confirms that the storytelling method is a humanistic and innovative pedagogical strategy in reducing communication barriers and improving students' speaking competence in the era of educational change.